1998
DOI: 10.1002/(sici)1097-0282(199812)46:7<433::aid-bip1>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Helical screw sense of peptide molecules: The pentapeptide system (Aib)4/L-Val[L-(αMe)Val] in the crystal state

Abstract: The crystal‐state preferred conformations of six Nα‐blocked pentapeptide esters, each containing four helicogenic, achiral α‐aminoisobutyric acid (Aib) residues followed by one chiral L‐valine (L‐Val) or Cα‐methyl‐L‐valine [(αMe)Val] residue at the C‐terminus, have been assessed by x‐ray diffraction analysis. In all of the compounds the (Aib)4 sequence is folded in a regular 310‐helical conformation. In the four pentapeptides characterized by the L‐(αMe)Val residue two conformationally distinct molecules occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 25 publications
(18 reference statements)
2
20
1
Order By: Relevance
“…Considering these results, both right‐handed and left‐handed helices are present in the equilibrium mixtures of these peptides in solution, and a slightly energetically favorable conformer is preferentially packed in the crystalline state. We conclude that the preference for a given helical handedness governed by side‐chain chiral centers, which affects achiral Aib‐based peptide segments is lower than that of L‐amino acids with an α‐chiral center4.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Considering these results, both right‐handed and left‐handed helices are present in the equilibrium mixtures of these peptides in solution, and a slightly energetically favorable conformer is preferentially packed in the crystalline state. We conclude that the preference for a given helical handedness governed by side‐chain chiral centers, which affects achiral Aib‐based peptide segments is lower than that of L‐amino acids with an α‐chiral center4.…”
Section: Discussionmentioning
confidence: 83%
“…It usually has a right‐handed ( P ) screw sense because of the asymmetric center of the α‐carbon of L‐α‐amino acids1. Several studies have attempted to control the helical screw sense of peptides2–10, and we have recently reported that a chiral cyclic α,α‐disubstituted α‐amino acid bearing only side‐chain chiral centers, (3 S ,4 S )‐1‐amino‐(3,4‐dimethoxy)cyclopentanecarboxylic acid [( S , S )‐Ac 5 c dOM ]11 controls the left‐handed ( M ) helical‐screw sense of its homopeptides12. Incidentally, α‐aminoisobutyric acid (Aib) is widely used as a strong helical inducer; however, it does not exhibit a helical‐screw sense bias because Aib is an achiral amino acid13–15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several studies have attempted to control the helical screw sense of Aib‐based oligopeptides . Furthermore, the screw sense control of helical Aib‐based peptides using a single chiral AA at the N‐terminus or C‐terminus has been investigated in the past decade . Recently, we reported that the hexapeptide Boc‐ l ‐Leu‐ l ‐Leu‐Aib‐ d ‐Leu‐ d ‐Leu‐Aib‐OMe [ tert ‐butoxycarbonyl (Boc), l ‐leucine ( l ‐Leu), d ‐leucine ( d ‐Leu), methyl ester (OMe)], which has two l ‐Leu, two d ‐Leu, and two achiral Aib, could form a left‐handed ( M ) 3 10 ‐helical structure in the crystalline state .…”
Section: Introductionmentioning
confidence: 99%
“…For the crystalline state, this has been proven by X-ray crystallography (e.g., [21] [22]). In spite of this knowledge, current interest in conformations of small peptides is documented by several recent reports (e.g., for pentapeptides [23] [24]).…”
mentioning
confidence: 99%